RESPONSIBILITY OF THE RECEIVING STATE IN PROTECTING THE DIPLOMATIC PREMISES (Case Of The Lowering Of The Iranian Embassy Flag In London) - Mela Yunita; Lily Husny Putri (Student Journal of International Law, 2022)
The responsibility of the receiving state in protecting the diplomatic premises has been regulated in the 1961 Vienna Convention on Diplomatic Relations. However, disturbances and destruction of diplomatic premises are still common in practice. One of them is the case of infiltration carried out by followers of al Shirazi against the Iranian embassy premise in London on Friday, March 9, 2018. The this paper indicates that the protection provided by the receiving state to the diplomatic representative premises in its country should not exceed the threat capacity or be less than the threat. In the case of lowering the flag of the Iranian embassy in London, this is a form of responsibility given by Britain as the recipient state, namely by arresting the intruders after the incident. However, the actions of the intruders constituted a violation of the 1961 Vienna Convention.